Adaptation of pavement deterioration models to Lithuanian automobile roads - Braga, Aivaras; Čygas, Donatas (Journal of Civil Engineering and Management, 2002)
The article presents three-system modelling of road pavement deterioration used in Lithuania: HDM-III (Highway Design and Maintenance Standards Model), HDM-4 (Highway Development and Management System) and DAVASEMA—Lithuanian pavement management system developed by Lithuanian Road Administration and based on HDM-III models. Using research data gathered in four years of the programme the authors analyse possibilities of adapting the pavement deterioration models to Lithuanian conditions. The article describes suggested procedures for calculating of calibration coefficients for the pavement deterioration models of the highest importance: road roughness component incremental model, structural cracking initiation model and structural cracking progression model. Frist Published Online: 30 Jul 2012